Investigation on root anatomy of rice plantation on coastal land - Pujiastuti, Pujiastuti; Elvira, Ajeng; Kuswati, Kuswati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.